A Complete Developmental Sequence of a Drosophila Neuronal Lineage as Revealed by Twin-Spot MARCM. - Yu, H.H.; Kao, C.F.; He, Y.; Ding, P.; Kao, J.C.; Lee, T. (PLoS Biology, 2010)
Drosophila brains contain numerous neurons that form complex circuits. These neurons are derived in stereotyped patterns from a fixed number of progenitors, called neuroblasts, and identifying individual neurons made by a neuroblast facilitates the reconstruction of neural circuits. An improved MARCM (mosaic analysis with a repressible cell marker) technique, called twin-spot MARCM, allows one to label the sister clones derived from a common progenitor simultaneously in different colors. It enables identification of every single neuron in an extended neuronal lineage based on the order of neuron birth. Here we report the first example, to our knowledge, of complete lineage analysis among neurons derived from a common neuroblast that relay olfactory information from the antennal lobe (AL) to higher brain centers. By identifying the sequentially derived neurons, we found that the neuroblast serially makes 40 types of AL projection neurons (PNs). During embryogenesis, one PN with multi-glomerular innervation and 18 uniglomerular PNs targeting 17 glomeruli of the adult AL are born. Many more PNs of 22 additional types, including four types of polyglomerular PNs, derive after the neuroblast resumes dividing in early larvae. Although different offspring are generated in a rather arbitrary sequence, the birth order strictly dictates the fate of each post-mitotic neuron, including the fate of programmed cell death. Notably, the embryonic progenitor has an altered temporal identity following each self-renewing asymmetric cell division. After larval hatching, the same progenitor produces multiple neurons for each cell type, but the number of neurons for each type is tightly regulated. These observations substantiate the origin-dependent specification of neuron types. Sequencing neuronal lineages will not only unravel how a complex brain develops but also permit systematic identification of neuron types for detailed structure and function analysis of the brain.